2021
DOI: 10.1021/jacs.1c08931
|View full text |Cite
|
Sign up to set email alerts
|

Emphanisis in Cubic (SnSe)0.5(AgSbSe2)0.5: Dynamical Off-Centering of Anion Leads to Low Thermal Conductivity and High Thermoelectric Performance

Abstract: The structural transformation generally occurs from lower symmetric to higher symmetric structure on heating. However, the formation of locally broken asymmetric phases upon warming has been evidenced in PbQ (Q = S, Se, Te), a rare phenomenon called emphanisis, which has significant effect on their thermal transport and thermoelectric properties. (SnSe)0.5(AgSbSe2)0.5 crystallizes in rock-salt cubic average structure, with the three cations occupying the same Wycoff site (4a) and Se in the anion position (Wyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 49 publications
3
47
0
Order By: Relevance
“…[2] Termed emphanisis, this behavior is prima facie surprising since the normal expectation is that symmetry increases on warming (i. e. decreases on cooling as in, e. g. the Jahn-Teller effect, though there are exceptions [3] ), whereas the opposite is observed in PbTe -there is a local decrease in symmetry at elevated temperature. Follow up work has shown that the local offcentering displacements are not random, but highly correlated [4] , with similar behavior observed in other chalcogenides [5] and even halide perovskites [6] .…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…[2] Termed emphanisis, this behavior is prima facie surprising since the normal expectation is that symmetry increases on warming (i. e. decreases on cooling as in, e. g. the Jahn-Teller effect, though there are exceptions [3] ), whereas the opposite is observed in PbTe -there is a local decrease in symmetry at elevated temperature. Follow up work has shown that the local offcentering displacements are not random, but highly correlated [4] , with similar behavior observed in other chalcogenides [5] and even halide perovskites [6] .…”
Section: Introductionsupporting
confidence: 68%
“…the Jahn-Teller effect, though there are exceptions 3 ), whereas the opposite is observed in PbTe -there is a local decrease in symmetry at elevated temperature. Follow up work has shown that the local off-centering displacements are not random, but highly correlated 4 , with similar behavior observed in other chalcogenides 5 and even halide perovskites 6 .…”
Section: Introductionsupporting
confidence: 67%
“…This is therefore not a standard phase transition and has been referred to as emphanisis. [33,34] The local distortion of Ag introduces a few extremely low frequency optical phonons at ≈20 cm −1 , resulting in a strong acousticoptical phonon scattering and an ultralow thermal conductivity of 0.26 W m −1 K −1 at 850 K in AgGaTe 2 . Our theoretical analysis suggests a large difference in energy between the s and d electron orbitals of the Ag leads to the weak sd 3 orbital hybridization, which is the driving force of the local distortion of Ag.…”
Section: Introductionmentioning
confidence: 99%
“…These results depict that the lattice parameters a and b are no longer equal in local scale for NPLs, as well as, for bulk samples and signify the presence of intrinsic local distortion in the RbPb 2 Br 5 lattice. 20 This local distortion in the average tetragonal structure may give rise to the strong lattice anharmonicity, 21,22 which will have impact on the luminescence properties. The selected area electron diffraction (SAED) pattern of the RbPb 2 Br 5 NPLs additionally confirms the single crystalline nature (Fig.…”
Section: Resultsmentioning
confidence: 99%